The Feasibility of Xpert MTB/RIF Testing to Detect Rifampicin Resistance among Childhood Tuberculosis for Prevalence Surveys in Northern China. (5th December 2017) - Lu, Jie; Li, Huimin; Dong, Fang; Shi, Jin; Yang, Hui; Han, Shujing; Chu, Ping; Zhao, Yanlin; Song, Wenqi; Guo, Yongli; Zhao, Shunying
Abstract : Drug resistance surveillance is crucial for control of drug-resistant tuberculosis (TB). However, limited data exists on the burden of drug-resistant TB in children. The goal of this work was to generate prevalence data regarding rifampicin- (RIF-) resistant childhood TB in northern China and to test the feasibility of Xpert for surveying pediatric TB drug resistance prevalence. We enrolled 362 clinically diagnosed childhood TB patients and collected sputum, gastric lavage aspirate (GLA), bronchoalveolar lavage fluid (BALF), and cerebral spinal fluid (CSF) samples. Xpert and solid culture were utilized to detect RIF resistance. The detection rate of Xpert-positive TB among new clinically diagnosed TB cases was 38.4% (139/362), significantly higher than that of solid culture-positive TB (16.3%, 59/362, P < 0.01 ). Notably, Xpert-positive rates differed significantly by sample type, with the highest positive rate for GLA (51.2%). The unit testing costs per RIF-resistant TB patient were $828.41 for solid culture and $761.86 for Xpert. Our data demonstrate that the prevalence of RIF resistance among childhood TB cases in our study (6.9%) is comparable to the national RIF resistance prevalence level of new cases (6.7%). In addition, Xpert is superior to the solid culture for RIF resistance survey in the childhood TB patients.